For Carlos Castillo-Chavez - Dean Evasius (Mathematical Biosciences and Engineering)
This volume, a tribute to the life and work of Carlos Castillo-Chavez on the occasion of his sixtieth birthday, stands for something greater than what can be presented in its pages. It is the man himself, who remains far above the words. The works collected here by people who know and admire Carlos are an attempt to convey some of his remarkable contributions and achievements.    I first met Carlos in 2005 as part of a visit he made to the National Science Foundation. Carlos had established a tremendous reputation by that time, and as a young program officer I was extremely pleased to have the opportunity to make small talk with him. He spoke about his students with an unmistakable passion and earnestness, and I wondered if this might be the key ingredient to his success in mentoring young scientists. In the years that followed I was able to see that Carlos channels his vitality into a remarkable capacity for work. The emails he sent to me over the years typically arrived at some odd hour of the night, perhaps suggesting a follow-up phone call for early the next morning. I'd call Carlos upon my arrival in the office and find him fully energized with the work of the new day.    The breadth of Carlos' impact is evident in the number of research and education communities that have honored and supported his work. At the National Science Foundation this includes programs spanning three Directorates: Mathematical and Physical Sciences, Biological Sciences, and Education and Human Resources. My interactions with Carlos came primarily in connection with his exceptional research programs for undergraduate and graduate students. His success in recruiting and mentoring underrepresented minorities in the mathematical sciences is almost without peer.    The founding of the Mathematical and Theoretical Biology Institute in 1996 and its subsequent development are rightly celebrated as landmarks in STEM education. What is remarkable is that this lifetime of work is just a fraction of what Carlos has accomplished!    His greatness lies in taking up the challenges that matter most. His most outstanding research contributions are grounded in stopping the spread of infectious diseases. His unparalleled mentoring of minority students is a reflection of his deep belief in the abundance of scientific talent.    Carlos, we in the mathematical sciences community offer you our deepest gratitude. Your legacy as a researcher and educator is already secure and it continues to grow. The immortality of your impact is assured by the timelessness of your research, and through the many alumni of your programs who are now making important contributions of their own. Best wishes for many more years of success!